Penerapan Pengendalian Manajemen Pada Penyaluran Pinjaman Koperasi Simpan Pinjam (Kospin) BN - Florentina Herispuspitasari; Ancella Anitawati Hermawan Anitawati Hermawan (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The distribution of loans to the construction sector is sometimes hampered by the capital they have. To improve the capital structure, Kospin will receive a loan from Cooperative Bank X. An increase in Kospin's capital must be followed by an adequate management control system. Therefore, the procedures for loan disbursement and performance measurement must be adequate. This research was conducted at Kospin BN to measure management control based on distribution procedures and performance measurement. The purpose of this study was to obtain an adequate loan operational procedure design, obtain a formal loan performance planning and measurement system as a key success factor to ensure and monitor the achievement of the strategy. The research method used is a case study, using qualitative analysis based on Boundary Systems and Diagnostic Control Systems. The results of the study, based on the SWOT analysis, there are weaknesses in management and pricing strategies as well as competitors' threats that hinder the business loan focus strategy. Therefore, Kospin should determine the right pricing strategy to win the competition. In addition, Kospin has not yet implemented the Business Loan SOP in accordance with the Decree of the Deputy for Financing of the Ministry of Cooperatives and SMEs No.06/Kep/Dep.2/II/2017. So it is necessary to adjust the linkages of procedures, personnel qualifications, division of tasks, business process flow, as well as documentation and records. Kospin also has not set performance targets, monitoring and measuring and evaluating performance formally. Kospin should set targets, monitor and measure performance and evaluate its performance.